STRATEGI PENGEMBANGAN INDUSTRI MEBEL CV â€œRUMAMBUN INDAHâ€ DI DESA TOULIANG OKI KECAMATAN ERIS KABUPATEN MINAHASA - Hera Ch. S. Ratulangi; Celsius Talumingan; Caroline B.D. Pakasi; Jenny Baroleh (COCOS, 2014)
ABSTRACTHera Ch. S. Ratulangi. The strategy of furniture industry development CV â€œRumambun Indahâ€ in Touliang Oki village Eris district Of Minahasa (regency under the supervision of Celsius Talumingan, as a chairman, Caroline B. D. Pakasi and Jenny Baroleh as the members).The objective of this research is to find out the potency and the the strategy of furniture industry development in Touliang Oki village Eris district of Minahasa. This research is worthwhile since furniture industries have contributed to the regional income of the district of MinahasaPrimary data were collected by interview during april, 2014 to August, 2014 by interview to respondent. SWOT analysis is3applied to analysis of furniture industry development strategy CV â€œRumambun Indahâ€.The results of this study indicated that the furniture industry CV â€œRumambun Indahâ€ has a potential to grow as indicated by analysis position which show that CV Rumambun Indah was in quadrant one that meant CV Rumambun Indah is in favorable situation to grow.